Inmates with Heat-Sensitive Health Conditions: Surveying Prisoner Litigation in the Age of Climate Change - Palacios, Jazmin E. (Criminal justice review, 2025)
Rising temperatures and severe heat, as a result of climate change, have led to a significant number of heat-related deaths and injuries among correctional populations in the United States. This article analyzes cases from the U.S. Circuit Courts of Appeals in which inmates challenged the constitutionality of their conditions of confinement in extremely hot facilities pursuant Title 42 U.S. Code Section 1983. An inductive analysis of caselaw revealed two themes: inmates with heat-sensitive health conditions and reasonable staff responses to inmate's heat exposure. The article concludes by offering policy guidance to prison officials based on the themes revealed in the circuit court decisions and by providing recommendations for future research.